Defects in Assembly of the Extracellular Matrix Are Responsible for Altered Morphogenesis of a Candida albicans phr1 Mutant - Popolo, Laura (American Society for Microbiology, 1998)
Analysis of Candida albicans cells using antibodies directed against Gas1p/Ggp1p, Saccharomyces cerevisiae homolog of Phr1p, revealed that Phr1p is a glycoprotein of about 88 kDa whose accumulation increases with the rise of external pH. This polypeptide is present both in the yeast form and during germ tube induction. In the Phr1(−) cells at pH 8 the solubility of glucans in alkali is greatly affected. In the parental strain the alkali-soluble/-insoluble glucan ratio shows a 50% decrease at pH 8 with respect to pH 4.5, whereas in the null mutant it is unchanged, indicating the lack of a polymer cross-linker activity induced by the rise of pH. The mutant has a sixfold increase in chitin level and is hypersensitive to calcofluor. Consistently with a role of chitin in strengthening the cell wall, Phr1(−) cells are more sensitive to nikkomycin Z than the parental strain.